KEPUASAN KONSUMEN Sunyi House Of Coffee And Hope - Berliana Adinda Lorenssa (2020)
This research, there is a quantitative descriptive method that is the consumer of Sunyi House of Coffee and Hope. This's coffee shop has employees with disabilities. This research has the purpose of knowing and analysing whether service quality, location, and facilities affect consumer satisfaction. The population in this research is the customers of Sunyi House of Coffee and Hope. Samples taken as many as 100 respondents with random sampling methods. Data collection through dissemination of questionnaires with descriptive and inferential data analysis techniques, and the analysis tool used is SmartPLS 3.0 (Partial Least Square). The result showed that (1) service quality affect customer satisfaction with a line coefficient value of 0,390. (2) location affect customer satisfaction with a line coefficient of 0.319. (3) facilities affect customer satisfaction with a line coefficient 0f 0,271.